The economic and health impact of a tax on sugar sweetened beverages (SSBs) in South Africa - Charity Gomo; Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
Background/Objectives: The increased consumption of sugar sweetened beverages (SSBs) has been associated with risks of obesity, and corresponding risks of type 2-diabetes, cancer, and cardiovascular disease. In order to reduce the intake of these beverages, the South African government has recently introduced a tax on SSBs. Methods: This paper evaluates the economic and health impact of the recently introduced tax on sugar sweetened beverages in South Africa, by constructing a microsimulation model using the South African Income and Household Survey (IES 2010/11) as the main data set. Results and conclusion: The overall results indicate that a 10% SSB tax will lead to a substantial reduction in consumption of carbonated soft drinks by about 27% and minor reductions in other SSB categories. Results also indicate that the 10% SSB tax can generate about ZAR 14.5 billion (USD 1.08 bn) in government tax revenue annually. In addition, simulation results show that the SSB tax would result in an average reduction in energy intake by 16.97 kj/person/day.
Keywords: 330